ИСТОЧНИКОВЕДЧЕСКИЕ АСПЕКТЫ ТЕОРИИ ГЕРМЕНЕВТИЧЕСКОГО ОПЫТА Х.–Г. ГАДАМЕРА (Zaporizhzhia Historical Review, 2021)
The article is devoted to the research of the source studies aspects of the theory of hermeneutics experience of H.-G. Gadamer. It has been demonstrated that philosophic hermeneutics doesn’t suggest the universal humanities method of cognition. It characterizes the conditions in which cognition is accomplished. H.-G. Gadamer has demonstrated that scientific method alone does not guarantee the truth, because our existence takes part in cognition